A Preliminary Investigation of Teacher-Reported Classroom-Level Adversity and Teacher–Student Interactions. (December 2021) - Granger, Kristen L.; Broda, Michael D.; Chow, Jason C.; McCormick, Nicholas; Sutherland, Kevin S.
Early elementary-age students with and at risk of emotional and behavioral disorders (EBD) tend to develop negative interaction patterns with their teachers. This preliminary study examines the extent to which symptoms of teacher burnout and teacher reports of classroom adversity are associated with the likelihood of negative interactions between teachers and students with and at risk of EBD. We conducted observations to assess teacher–student interactions in individual and group settings, and teachers reported on burnout and classroom adversity. This study included 10 teachers and 15 of their students with or at risk of EBD. High levels of classroom adversity increased the likelihood of negative teacher–student individual interaction. High levels of classroom adversity modified the relation between personal accomplishment and negative teacher–student interactions in group settings. Findings suggest teachers may need additional support for engaging in high-quality interactions with students with and at risk of EBD, particularly in classrooms facing high levels of adversity, and inform intervention design and implementation.